International Hotel Systems (IHS) As A Research Problem in Polish and Foreign Languages Scientific Literature - Malgorzata JANIAK; Marzena MAKOWSKA-ISKIERKA (Communications of International Proceedings, 2022)
Apart from travel, the hotel industry is the part of tourism that generates the largest expenses in the tourist's outlays and that may have many positive implications for local markets (Yin, Hastings, 2007). The modern hotel market is largely controlled by a dozen or so global hotel systems that compete year after year for the priority to be the largest player on the market (both in terms of the number of hotels or number of rooms). International hotel systems (IHS) affect the activities of the entire industry in a variety of ways, including entering new markets, shaping trends, implementing innovations in the field of products offered or management methods, adjusting innovations to changes taking place in society and economy, responding to the activities of competitors. The aim of the article is to check the current state of knowledge related to the activities of IHS and to show how important it is to conduct research in this area. In this work, the Authors used only scientific literature (Polish and foreign), without making use of trade literature.
Keywords: International hotel systems; hospitality; spatial location; location theories; literature review